Effects of acidification and nitrate eutrophication on the widespread soft coral Xenia umbellata - Lorena Braxator; Arjen Tilstra; Soh Young Kim; Christian Wild (PANGAEA, 2025)
Coral reefs may experience lower pH values as a result of ocean acidification, which has negative consequences for many reef organisms and may be exacerbated by other factors such as eutrophication. Thus far, the effects of these global (acidification) and local (eutrophication) factors have been mainly investigated separately, and previous research concentrated on hard corals. We thus carried out a manipulative aquarium experiment for 21 days to study the response of the widespread pulsating soft coral Xenia umbellata to ocean acidification (stepwise decrease from ambient (8.2) to pH values of 8.0, 7.8, and 7.6) and nitrogen eutrophication, i.e., nitrate concentrations were increased from ambient (< 0.5 μM) to ~5 μM. The effects of these single factors, as well as their combination, on the ecophysiology of X. umbellata were assessed by monitoring the response variables survival, growth rate, pulsation rate, coloration, photosynthesis and respiration, and Symbiodiniaceae cell densities over time. Under acidification, both growth- and pulsation rates significantly decreased by 50 and 25 %, respectively, compared to controls, while the other response variables remained unaffected. Surprisingly, none of the response variables showed a significant change when X. umbellata fragments were exposed to nitrate alone. The addition of nitrate to acidified waters had no interactive effects. Our findings indicate that the investigated soft corals were not affected by nitrate addition and only to some extent by ocean acidification or the combination of both factors. These results contribute to explain the competitive advantage that soft corals may have over hard corals, as currently reported from many reef locations in the Indo-Pacific.